Closed Mode Separation of the Symmetrical Structure / Mohamad Azam Shah Aziz Shah...[et al.] - Shah Aziz Shah, Mohamad Azam; Yunus, Mohd Azmi; Abdul Rani, Muhamad Norhisham; Tormodi, Nor Azela (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Structural modifications based on vibration analysis are very important in structural optimization of the system in order to modify the dynamics behaviour of the structure. Symmetrical shape structures are prone to close natural frequencies and it is vitally important to identify the mode shapes structure that are near to the desired operating frequency by moving the unwanted modes away from the concern region. The identification of mode shapes that are close in natural frequencies are very difficult to distinguish and do not correspond closely to the numerical prediction. In order to identify modes of the close frequencies, the experimental method of mass modifications will be used to modify dynamic properties of the structure. The objective of this project is to study the closed mode of the I-shape structure and to change the dynamic characteristics by mass modifications so that the mode shapes can be distinguished. The finite element model of the symmetrical shape structure is constructed using FE software packages and compared with the experimental data from LMS SCADAS software. The measured dynamic behaviour is obtained using an impact hammer testing and roving accelerometers under free-free boundary conditions. The results obtained from the predicted and experimental show that mass modification on the nodal point can be used to alter the natural frequencies without changing the mode shapes of the structure. It is believed that the dynamic characteristics of the symmetrical structure can be change by manipulating the mass of the structure.